Naming Motives Of Uzbek First Names And Their Comparison With German Surname Motives - Ziyodbek Abdullaev (Zien Journals, 2023)
In this article, the motifs of Uzbek names and their similarities with motifs of German surnames are scientifically analyzed in a comparative aspect. Names in German have their meaning over time due to its loss, the clarity of the meanings of names in the Uzbek language has decreased
Keywords: name; surname; motive